Intelligent components and instruments for control applications 1994 : 2nd IFAC Symposium, Budapest, Hungary, 8-10 June 1994 - Banyasz, Csilla (IFAC Postprint Volume., 1994)
Advances in computer technology and sensor development have led to increasingly successful control operations. In order to maximize future potential it is vital for academics and practitioners in the field to have an international forum for discussion and evaluation of the latest developments. The IFAC Symposia on intelligent components and instruments provide this opportunity and the latest in the series gives rise to this invaluable publication which provides an authoritative assessment of the present state and future directions of these key technologies.